Novel receiver structures for cooperative communication systems - Wei, Shuyang (Nanyang Technological University, 2020)
Because of the fast development of wireless communication as well as popularity of mobile devices, people’s life has changed greatly. How to provide a faster and more stable communication is always an important problem for researchers. Cooperative communication is developed because of the advantages of larger cell size and more reliable diversity channel. Amplify-and-forward (AF) protocol and decode-and-forward (DF) protocol are two major relaying protocols for cooperative communication. In this dissertation, we study the performance of the two protocols in terms of bit error rate and discuss the limitation of fixed relaying and selective relaying for these two protocols. The performance of improvement method with channel coding is studied and analyzed. To combat with the severe error propagation for the DF protocol, a hybrid method of the two protocols is studied and the performance of the hybrid method is analyzed and compared with the SNR threshold DF protocols and AF protocols. We find out that, the hybrid method can achieve almost the same bit error rate with the SNR threshold DF protocol with an easier structure of fixed relaying. Both bit error rate on Rayleigh fading channel as well as Rician fading channel are simulated in this dissertation.